2016
DOI: 10.3390/e18040147
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical Simulation of Williamson Combined Natural and Forced Convective Fluid Flow between Parallel Vertical Walls with Slip Effects and Radiative Heat Transfer in a Porous Medium

Abstract: Numerical study of the slip effects and radiative heat transfer on a steady state fully developed Williamson flow of an incompressible Newtonian fluid; between parallel vertical walls of a microchannel with isothermal walls in a porous medium is performed. The slip effects are considered at both boundary conditions. Radiative highly absorbing medium is modeled by the Rosseland approximation. The non-dimensional governing Navier-Stokes and energy coupled partial differential equations formed a boundary problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The non-dimensional first order differential governing Equation (48) is solved numerically by using the Runge-Kutta-Fehlberg method with shooting technique [51] for various finite boundary layer lengths. The grid size of 0.01 is chosen were the maximum change in final value is less than 10 −4 .…”
Section: Resultsmentioning
confidence: 99%
“…The non-dimensional first order differential governing Equation (48) is solved numerically by using the Runge-Kutta-Fehlberg method with shooting technique [51] for various finite boundary layer lengths. The grid size of 0.01 is chosen were the maximum change in final value is less than 10 −4 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the mathematical study was performed to figure out the slip effects and radiation in a fully developed incompressible Newtonian fluid Williamson flow. 8 Moreover, the Duwairi et al 9 found that the increase in squeezing and extrusion of a viscous fluid in an unstable approach between two parallel plates at fixed temperature caused a decrease in the fluid velocity and enhanced the rates of heat transfer. Additionally, Kausar et al 10 studied the Darcy_Brinkman flow across a stretched sheet in the existence of frictional heating and porous dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…The ship maneuver-induced motion in the partially-filled tanks by liquid, sloshing poses a thoughtful danger to the controllability and stability of this phenomenon. The entropy generation minimization method is used for the design of fluid flow motion system [1] as well as thermal systems [2][3][4] in recent years. Although the method is applied to the thermodynamic optimization of many finite-size systems and finite-time processes [5], the application in isothermal fluid flow is rare [6].…”
Section: Introductionmentioning
confidence: 99%